Implications of Small Bargaining Units and Enterprise Unions on Bargaining Disputes: A Look into the Future? - Hebdon, Robert; Hyatt, Douglas; Mazerolle, Maurice (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1999)
Using a large data set of large and small bargaining units, this paper examines the implications for collective bargaining disputes of the evolution toward small bargaining units and the move to nontraditional forms of representation. It is found that smaller bargaining units, as well as independent unions in both the public and private sectors, are less likefy to reach an impasse. This finding supported those hypothesizing the cooperative nature of these organizations. These two sets of results suggest that the movement to smaller bargaining units, and towards more independent representation, will result in a higher proportion ofdirectly negotiated settlements in the future. However, a reduced incidence of impasse does not necessarily mean a reduction in industrial conflict. We found evidence of a shift away from a collective expression of conflict such as strikes, to more individual expressions. Thus, in the future, there may be a greater need for internal conflict resolution Systems.